It’s all about the medium: dissemination of crisis communication and the effects on organizational reputation - Franklin, Ambrosia (Kansas State University, 2014)
As technology advances in social media, crisis management professionals and researchers are charged with revamping or discovering new communication tools to address the dissemination crisis information. Social media provides a platform for open conversations, community, and connectedness among individuals and permits anyone to become the source of information during a time of crisis. Crisis news can be shared and reshared among millions of people without the need of a professional source, such as a journalist. A crisis may disrupt social order to an organization’s reputation and legitimacy, but a crisis also provides an opportunity for growth or renewal. Previous literature has analyzed crisis communication affects on organizational reputation through cases studies; however, there is lack of analysis in using an experimental design. Through an experiment with 207 undergraduate students, this study empirically evaluates the dissemination of crisis communication through Twitter and its effect on organizational communication. Using McLuhan’s (1967) concept of the medium is the message, this study highlights past findings, explicates types of crises, and focuses on the medium as a variable (not content of response) of interest to provide groundwork for an experimental inquiry into how the medium itself (as opposed to message content) impacts the efficacy of organizational crisis responses. A 2x3 experimental design with two research conditions- types of crisis: (1) intentional and (2) unintentional and source types: (1) organization (2) journalist, and (3) friend was used in this study. An online questionnaire was administered through an online survey service to approximately 2,000 undergraduates. Participants were randomized in one of six conditions based on the type of crisis (unintentional and intentional) and the source (organization/journalist/friend) of the message and directed to read an unintentional or intentional press release. Findings indicated that the perception of responsibility is a valid factor to consider during a possible crisis. Overall, as the previous studies have concluded, the organization is perceived as responsible for the crisis.
Keywords: Crisis Communication; Social Media; Organizational Reputation; Twitter; Mass Communications (0708)